2013
DOI: 10.3109/10428194.2013.794944
|View full text |Cite
|
Sign up to set email alerts
|

Expression of CD203c on basophils as a marker of immunoglobulin E-mediatedl-asparaginase allergy

Abstract: Immediate allergy to l-asparaginase (ASP) is a major obstacle in treating lymphoid malignancies. ASP-specific immunoglobulin G (ASP-IgG) has been used as a surrogate marker. Recently, the CD203c-basophil activation test (BAT) was found to be useful in diagnosing IgE-mediated allergies. We compared the diagnostic utility of the CD203c-BAT to that of ASP-IgG levels in determining ASP allergies in children. Eight ASP allergic reactions occurred over 75 ASP treatment courses. The sensitivity, specificity and area … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…( 9 ) In addition, it has been reported that CD203c is a useful marker for allergies induced by amoxicillin and (L)-asparaginase. ( 10 , 11 ) We recently confirmed that patients with a history of CBDCA-induced severe HR showed an increase in CD203c-positive basophils compared with patients without HR. ( 12 ) In addition, all five patients with grade 2 or higher HR showed increased CD203c on basophils during the months following the onset of HR, whereas no such increase was not observed in the previous courses of CBDCA.…”
mentioning
confidence: 68%
“…( 9 ) In addition, it has been reported that CD203c is a useful marker for allergies induced by amoxicillin and (L)-asparaginase. ( 10 , 11 ) We recently confirmed that patients with a history of CBDCA-induced severe HR showed an increase in CD203c-positive basophils compared with patients without HR. ( 12 ) In addition, all five patients with grade 2 or higher HR showed increased CD203c on basophils during the months following the onset of HR, whereas no such increase was not observed in the previous courses of CBDCA.…”
mentioning
confidence: 68%
“…Recently, it has been shown that BAT is a useful marker for identifying l -asparaginase allergy because of its high sensitivity and specificity, and combining the BAT with an l -asparaginase-specific IgG assay is the most accurate method of identifying l -asparaginase allergy. 30 …”
Section: Discussionmentioning
confidence: 99%
“…Upon basophil activation, these two markers are commonly upregulated with similar kinetics, but they have distinct characteristics from each other. CD63 has been better validated for drug allergies; however, CD203c is increasingly utilized in recent studies [ 15 , 23 , 34 , 35 , 48 , 51 , 60 ]. Upon anaphylactic stimulation, there is degranulation that causes CD63 to appear at the cell surface during the process of fusion of main granules with plasma membranes [ 2 ].…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies [ 60 - 64 ] examined the outcome of BAT in patients with hypersensitivities to antineoplastic, biologic agents, or other drugs ( Table 6 ). L -Asparaginase allergies were assessed using CD203c expression and were found to have high sensitivity (75%) and negative predictive value (96%) [ 60 ]. One case study also reported the potential utility of BAT in cisplatin hypersensitivity [ 65 ].…”
Section: Clinical Applicationsmentioning
confidence: 99%